The perception of inclusive education professionals concerning Occupational Therapy - Ana Paula Morais Braga; Andrezza Fernandes de Andrade (Universidade de Fortaleza, 2009)
Objective: To investigate the level of knowledge of two principals and four teachers of public schools from a city in Ceará, concerning the Occupational Therapy in the process of school inclusion, showing the level of formation of these professionals regarding inclusive education. Method: A field research, with a qualitative interventionist approach, using the comparative method. Interviews were carried out as well as interventions by means of lectures and group dynamics dealing with subjects referring to Occupational Therapy in inclusive education. The data were evaluated by the technique of content analysis. Results: The results showed that, after the accomplishment of all interventions, the participants begun to know and to identify the profession, mainly its actions in the field of inclusive education. We point out the need of improvement as well as of specialization for the subjects, since they do not receive enough qualification to act in this new area of inclusive education. Conclusion: In the studied sample, the subjects know the process of school inclusion; however they neither have profound knowledge in the area nor the formation for inclusive practice.